The Influence of Leadership Style, Job Satisfaction, and Work Discipline on Employee Performance at Hotel Puri Santrian Sanur - HENDRAWAN, I Made Galih; SETENA, I Made; DEWI, Made Pratiwi (Journal Management and Hospitality, 2023)
The following research was conducted based on the issues occurring at the research site, specifically regarding the number of tourist visits to Hotel Puri Santrian Sanur, which has changed yearly. This research aims to test and analyze the influence of leadership style, job satisfaction, and work discipline on employee performance. With a total sample of 85 respondents processed using a saturated census technique, all data obtained from the distributed questionnaires were deemed suitable. The data were then analyzed using multiple linear regression and hypothesis testing (F-test and t-test) processed with SPSS 26. The study results indicate that leadership style, job satisfaction, and work discipline positively and significantly affect employee performance at Hotel Puri Santrian Sanur. Leadership style, job satisfaction, and work discipline have a significant impact on employee performance at Hotel Puri Santrian Sanur. Leadership style positively and significantly affects employee performance at Hotel Puri Santrian Sanur. Job satisfaction positively and significantly influences employee performance at Hotel Puri Santrian Sanur. Work discipline positively and significantly affects employee performance at Hotel Puri Santrian Sanur.